PEMBENTUKAN KATA PADA GAIRAIGO DALAM LIRIK LAGU KARYA MR.CHILDREN - Meirinda, Alya Putri; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to analyze the word formation process in gairaigofound in the song lyrics of the Japanese band Mr.Children. Gairaigo refers to loanwordsthat have been adapted into Japanese from foreign languages. The study uses acombined approach of the theories by Tsujimura and Kridalaksana. The data used inthis study were obtained from the song lyrics of Mr.Children that contain gairaigo. Theresults of the analysis show that the word formation process in gairaigo involves severallinguistic mechanisms, namely affixation, compounding, and abbreviation. Theaffixation process is seen in the phonetic changes of gairaigo, which are adapted byadding certain suffixes to change the word class or meaning. Compounding is alsofound in some gairaigo, where two foreign words are combined into a new word formthat aligns with the phonetic structure of the Japanese language. Furthermore,abbreviation occurs when a loanword is shortened or abbreviated to make it easier topronounce or more compatible with the phonological structure of Japanese. The resultsof this study provide an overview of how the Japanese language adapts foreignvocabulary in ways that are consistent with the phonetic and morphological structure ofJapanese.Keywords: Gairaigo, Word Formation, Affixation, Compounding, Abbreviation, Mr.Children.